PENEGAKAN HUKUM TERHADAP TINDAK PIDANA PHEDOFILIA DI WILAYAH HUKUM POLISI RESOR KOTA PEKANBARU - Tri Novita Sari Manihuruk; Emilda Firdaus; Erdiansyah ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Phedofilia is acts of infringement of the rights of children are classified as vile and evil. Increased Phedofilia criminal act in Indonesia, especially in Pekanbaru become a serious problem currently faced. Therefore Phedofilia should be addressed in a rational way. One rational efforts is with law enforcement policies. The purpose of this study are to know the law enforcement against criminal acts of Phedofilia in jurisdiction of Police Pekanbaru City resort, to know the police barriers in law enforcement against criminal acts of Phedofilia in jurisdiction of Police Pekanbaru City resort, and to know the efforts made of Police to overcome obstacles in law enforcement against criminal acts of Phedofilia in jurisdiction of Police Pekanbaru City resort. This type of research is a juridical sociological research, the data sources used, the primary data, secondary data and data tertiary, data collection techniques in this study with interviews and literature study. Law enforcement against criminal acts of Phedofilia in jurisdiction of Police Pekanbaru City resort not running optimally because of the presence of obstacles, obstacles encountered in law enforcement against criminal acts of Phedofilia in jurisdiction of Police Pekanbaru City resort is in the form of internal factors and external factors, efforts to overcome this barrier is increasing the number of personnel investigator PPA and increase knowledge of investigator in understanding the psychology of the child. And formed cooperation between the police and the school psychologist incredible, take the autopsy report as evidence and search and publish wanted list (DPO).Keywords : Law Enforcement - Criminal Act - Phedofilia